Identification of the probable site of choleragen-catalyzed ADP-ribosylation in a Go alpha-like protein based on cDNA sequence. - Angus, C W (1986)
Go alpha, a 39-kDa guanyl nucleotide-binding protein, is functionally and structurally similar to the alpha subunits of the stimulatory and inhibitory guanyl nucleotide-binding proteins (Gs alpha, Gi alpha) of adenylate cyclase and to the alpha subunit of transducin (T alpha), the guanyl nucleotide-binding protein of the retinal photon reception system. A cDNA clone was isolated from a bovine retinal lambda gt10 library by using oligonucleotide probes complementary to sequences in two putative T alpha clones. Partial sequence analysis revealed a deduced amino acid sequence identical to sequences of four tryptic peptides from bovine brain Go alpha. Gs alpha and T alpha are known to serve as substrates for ADP-ribosylation by choleragen. Other workers have established the sequence of the tetrapeptide in T alpha containing the arginine that is ADP-ribosylated and its location in the amino acid sequence deduced from T alpha cDNA. The Go alpha cDNA described here includes a region encoding an amino acid sequence very similar to that surrounding the ADP-ribosylation site in T alpha, consistent with observations that Go alpha can also be a substrate for choleragen. A corresponding sequence in the recently identified Gs alpha cDNA is less homologous to that in T alpha or Go alpha. The reported differences in conditions that promote choleragen-catalyzed ADP-ribosylation of Gs alpha vs. Go alpha could be related to differences in amino acid sequence in the region of the acceptor arginine.